2018
DOI: 10.1200/jco.2018.79.1483
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemoradiotherapy Followed by Surgery Versus Surgery Alone for Locally Advanced Squamous Cell Carcinoma of the Esophagus (NEOCRTEC5010): A Phase III Multicenter, Randomized, Open-Label Clinical Trial

Abstract: PurposeThe efficacy of neoadjuvant chemoradiotherapy (NCRT) plus surgery for locally advanced esophageal squamous cell carcinoma (ESCC) remains controversial. In this trial, we compared the survival and safety of NCRT plus surgery with surgery alone in patients with locally advanced ESCC.Patients and MethodsFrom June 2007 to December 2014, 451 patients with potentially resectable thoracic ESCC, clinically staged as T1-4N1M0/T4N0M0, were randomly allocated to NCRT plus surgery (group CRT; n = 224) and surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
673
11
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 640 publications
(766 citation statements)
references
References 22 publications
(25 reference statements)
17
673
11
10
Order By: Relevance
“…More than 90% of esophageal cancer cases have been classified as esophageal squamous cell carcinoma (ESCC) in China and esophageal adenocarcinoma is the predominant type in Western countries . Despite advances made in chemoradiotherapy for ESCC, esophagectomy is still the most effective treatment measure at present . However, more than half of the patients who undergo radical esophagectomy develop locoregional or distant recurrence within three years …”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of esophageal cancer cases have been classified as esophageal squamous cell carcinoma (ESCC) in China and esophageal adenocarcinoma is the predominant type in Western countries . Despite advances made in chemoradiotherapy for ESCC, esophagectomy is still the most effective treatment measure at present . However, more than half of the patients who undergo radical esophagectomy develop locoregional or distant recurrence within three years …”
Section: Introductionmentioning
confidence: 99%
“…Third, the necrosis and fibrosis of tumor tissue after neoadjuvant chemoradiotherapy greatly reduces active tumor cells and the probability of tumor cells shedding, spreading, and planting during surgery, thereby reducing local recurrence rates. Compared with esophagectomy alone, several randomized studies have indicated that this neoadjuvant chemoradiotherapy improves pCR, locoregional control, and survival in patients with esophageal cancer undergoing esophagectomy …”
Section: Discussionmentioning
confidence: 99%
“…Compared with esophagectomy alone, several randomized studies have indicated that this neoadjuvant chemoradiotherapy improves pCR, locoregional control, and survival in patients with esophageal cancer undergoing esophagectomy. 1,2,7 Conventional fractionated radiotherapy has become the mainstay of preoperative radiotherapy in esophageal cancer. However, the extension of preoperative treatment time and the increase of treatment cost is an issue that must be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations